Bacterial Membrane Vesicles as Mediators of Microbe – Microbe and Microbe – Host Community Interactions - Caruana, Julie C.; Walper, Scott A. (Frontiers in Microbiology, 2020)
Bacterial membrane vesicles are proteoliposomal nanoparticles produced by both Gram-negative and Gram-positive bacteria. As they originate from the outer surface of the bacteria, their composition and content is generally similar to the parent bacterium’s membrane and cytoplasm. However, there is ample evidence that preferential packaging of proteins, metabolites, and toxins into vesicles does occur. Incorporation into vesicles imparts a number of benefits to the cargo, including protection from degradation by other bacteria, the host organism, or environmental factors, maintenance of a favorable microenvironment for enzymatic activity, and increased potential for long-distance movement. This enables vesicles to serve specialized functions tailored to changing or challenging environments, particularly in regard to microbial community interactions including quorum sensing, biofilm formation, antibiotic resistance, antimicrobial peptide expression and deployment, and nutrient acquisition. Additionally, based on their contents, vesicles play crucial roles in host-microbe interactions as carriers of virulence factors and other modulators of host cell function. Here, we discuss recent advances in our understanding of how vesicles to function as signals both within microbial communities and between pathogenic or commensal microbes and their mammalian hosts. We also highlight a few areas that are currently ripe for additional research, including the mechanisms of selective cargo packaging into membrane vesicles and of cargo processing once it enters mammalian host cells, the function of vesicles in transfer of nucleic acids among bacteria, and the possibility of engineering commensal bacteria to deliver cargo of interest to mammalian hosts in a controlled manner.